Optimization of the Dikmas Lantas Kamsel Unit to Reduce the Number of Traffic Violations in the Jurisdiction of Boyolali Police Station - Lubis, Muhammad Fathur Alfarizi (Advances in Police Science Research Journal, 2024)
Traffic violations are one of the traffic problems in Boyolali Regency. Preventive efforts through Traffic Public’s Education have been carried out by the Police Security and Safety Unit it of Boyolali Police, but the number of traffic violations is still high and increases every year, so it is necessary to optimize the Traffic Public’s Education Police Security and Safety Unit of Boyolali Police to reduce the number of traffic violations. This final project research was conducted in the Boyolali Police area using a qualitative approach. In order to discuss the formulation of these problems, the author uses an analysis knife in the form of several theories and concepts, including management theory, SWOT Analysis theory and the concept of Traffic Public’s Education and traffic violations. The results showed that the implementation of Traffic Public’s Education and the efforts made by the Police Security and Safety Unit, especially in reducing the number of traffic violations in the jurisdiction of Boyolali Police Station, were still not optimal. This is caused by several factors, including personnel problems, facilities and infrastructure, and the implementation of the Traffic Public’s Education which is not appropriate and the determination of Traffic Public’s Education targets that have not been targeted. Researchers suggest optimization efforts in the form of adjusting the number and increasing the competence of the Boyolali Police Security and Safety Unit, improving the methods of Traffic Public’s Education both visually, audio or audio visual, the material for implementing Traffic Public’s Education is more emphasized on instilling awareness for orderly driving, procuring facilities and infrastructure to support the implementation of Traffic Public’s Education and establishing good cooperation with local government and private parties in supporting the implementation of Traffic Public’s Education of the Boyolali Police Security and Safety Unit.